THE ROLE OF HUMANITARIAN TRAINING OF FUTURE SPECIALISTS IN THE FINANCIAL SPHERE - Pavlenko, Ilya (SWorld-Ger Conference proceedings, 2023)
The general trend in the global development of higher education is to strengthen the role of humanities education. Formation of students' humanitarian thinking will make it possible to move away from monopolization of assessments of social processes and p